PERKEMBANGAN KEMAMPUAN BAHASA ANAK USIA 4-5 TAHUN MELALUI BERCERITA SEDERHANA DITINJAU DARI SEGI ASPEK SINTAKSIS DAN SEMANTIK - Atik Mufidah Atik (Generasi Emas: Jurnal Pendidikan Islam Anak Usia Dini, 2021)
The development of language skills in children aged 4-5 years often experience obstacles in conversation, delivery or expression and talking to other people. The problem that occurs in children aged 4-5 years in the A6 group RA Muslimat NU Masyithoh 05 Banyurip Ageng Pekalongan City is that the development of children's language skills in terms of syntactic and semantic aspects of children is still not well developed. The purpose of simple storytelling activities is to determine the development of children's language skills, especially in the syntactic and semantic aspects. The research method uses a qualitative descriptive method. The research site is at RA Muslimat NU Masyithoh 05 Banyurip Ageng, Pekalongan City. The research period is from May 29 to June 11, 2021. The research subjects were 2 students in group A6 with an age range of 4-5 years with data sources from 15 students. Data collection techniques using observation, interviews, and documentation. The results of a study conducted for approximately 2 weeks with a sample of 2 children showed that through simple storytelling, children aged 4-5 years old could develop language skills.